The Effect of Multiball Training on The Target Accuracy of Forehand Strokes and Backhand Drives of Table Tennis Games: Literature Review - Fadjri, Mukharrar; Primasoni, Nawan; As, Jusrianto (Asian Journal of Social and Humanities, 2023)
Table tennis is a sport that has been popular in the community and loved by the community. This can be seen both in cities and in the countryside, where people of different ages participate in table tennis games, both men and women. The purpose of using this method is to obtain information by the power of scientific sources. This research review is taken from journals, articles, books or literature reviews that are relevant to the content of related problems. Analysis data collection techniques using Google Scholar Database, Science Direct and Pubmed. Meta-analysis is a method for summarizing various research results quantitatively. After reviewing research materials from selected journals, the next step is to analyze and discuss the journal. In this review, 10 journals were examined in an article analysis, consisting of five international journals and five national journals Peer-reviewed journals have publication years between 2015 and 2022. experiments, surveys, and meta - Analysis is used as a research method. The average subject in this study was about 5 to 40 subjects. Based on a review of data analysis results from 10 journals, it can be concluded that training using the multiball method can provide results and increase skills or skills in forehand drive and backhand drive of table tennis games